Exploration of Electrochemical Intermediates of the Anticancer Drug Doxorubicin Hydrochloride Using Cyclic Voltammetry and Simulation Studies with an Evaluation for Its Interaction with DNA - Partha Sarathi Guin; Saurabh Das (International Journal of Electrochemistry)
Electrochemical behavior of the anticancer drug doxorubicin hydrochloride was studied using cyclic voltammetry in aqueous medium using Hepes buffer (pH~7.4). At this pH, doxorubicin hydrochloride undergoes a reversible two-electron reduction with E1/2 value −665±5 mV (versus Ag/AgCl, saturated KCl). Depending on scan rates, processes were either quasireversible (at low scan rates) or near perfect reversible (at high scan rates). This difference in behavior of doxorubicin hydrochloride with scan rate studied over the same potential range speaks of differences in electron transfer processes in doxorubicin hydrochloride. Attempt was made to identify and understand the species involved using simulation. The information obtained was used to study the interaction of doxorubicin hydrochloride with calf thymus DNA. Cathodic peak current gradually decreased as more calf thymus DNA was added. The decrease in cathodic peak current was used to estimate the interaction of the drug with calf thymus DNA. Nonlinear curve fit analysis was applied to evaluate the intrinsic binding constant and site size of interaction that was compared with previous results on doxorubicin hydrochloride-DNA interaction monitored by cyclic voltammetry or spectroscopic techniques.